Огляд сучасних моделей розвитку корозійних пошкоджень та напрямів дослідження їх впливу на міцність і надійність елементів трубопровідних систем - Потопальська, Ксенія Євгенівна (НТУ "ХПІ", 2016)
У даній роботі приводиться огляд сучасного стану досліджень в області корозійно пошкоджених трубопроводів. Розглядаються підходи для аналізу міцності та надійності магістральних трубопроводів з дефектами. Виділено два основних напрямки до дослідження даних конструкцій: це підходи в яких аналіз надійності проводиться на основі оцінки зміни фізико-механічних властивостей матеріалу, та ті, в яких за допомогою сучасних програмних комплексів з використанням методу скінченних елементів проводиться явне моделювання пошкоджених трубопроводів та визначається напружено-деформований стан та залишковий ресурс конструкції.

The analysis of current research in the field of reliability analysis, corrosion damaged pipelines was made in this paper. The methods used to determine the life-time of pipelines have been divided into two groups: those in which the reliability analysis is based on the assessment of changes in physical and mechanical properties of the material, and those which are used the finite element method made a explicit modeling of damage on surface of pipelines, where by the numerically defined characteristics of stress strain state and analyzes the strength and reliability. From the analysis of works was defined, appearance of corrosion defects on the surface of the pipeline leads to plastic deformation even at relatively small size of damage, and speed up the development of corrosion. This suggests that in the determination of residual life, it is necessary to use methods of accumulation is low cyclic fatigue.
Review of modern models of development of corrosion damage and research tendency of their influence to strength and reliability of elements of pipeline systems
Keywords: магістральний трубопровід; корозія; пошкодження; надійність; корозійний дефект; pipeline; corrosion; damage; reliability; corrosion defects